Methanolysis on extracted sapfrom inner and outer part of core oil palm trunk using phosphomolybdic acid and aluminium sulphate - Jahar N.A.; Mostapha M.; Wong J.C.; Jaafar S.N.S.; Pua G.; Zakaria S.; Chia C.H. (American Institute of Physics Inc., 2023)
Concentration of extracted free sugar in the oil palm trunk from inner and outer part was analysed using High Performance Liquid Chromatography (HPLC). The highest sugar concentration was glucose and total sugar content was higher in the inner part than the outer part. The methanolysis reaction of extracted sapfrom inner and outer part of core oil palm trunk using phosphomolybdic acid and aluminium sulphate was done using methanol as solvent, 2.5 h and at 160C. In this reaction, conversion of total sugar produced high concentrations of pentanoic acid, 4-oxo-, methyl ester and low 5-hydroxymethylfurfural using aluminium sulphate as catalyst. 2016 Author(s).